Critical Mass : The Dangerous Race for Superweapons in a Fragmenting World - Burrows, William E. 1937- and Windrem, Robert (New York Simon and Schuster, 1994)
The spread of superweapons - nuclear, chemical, and biological - and the means to deliver them is now out of control and is the single greatest danger facing the world. Critical Mass is the first comprehensive look at how this happened, where current and potential threats are, and what can be done to avert catastrophe. Third World superweapon proliferation is more frightening than the cold war arms race. This new arms race is a genocidal contest, fueled by hatred and meant to settle old racial, ethnic, and religious scores. Authors William E. Burrows and Robert Windrem disclose how Saddam Hussein planned an assembly line of fifteen to twenty atomic bombs a year, provided by an Arab Dr. Strangelove and atomic spies, cynical German industrialists with Nazi heritages, greedy Brazilian businessmen, and an impressive procurement network of arrogant Western politicians and Ph. D.s who consulted on death. Iraq is now a model for nations from Kazakhstan to North Korea, from Iran to India to Indonesia, nations that see Mutual Assured Destruction not as a deterrent but as a temptation. Dealing with proliferation, the authors say, is now Washington's highest foreign policy priority. Success will depend not so much on "techno-fixes" such as export controls as on resolving the underlying issues that divide the Third World.
Include Notes and Index
Keywords: Nuclear weapons -- World politics